Favorable Glycemic Control with Once-Daily Insulin Degludec/Insulin Aspart after Changing from Basal Insulin in Adults with Type 2 Diabetes - Han Na Jang; Ye Seul Yang; Seong Ok Lee; Tae Jung Oh; Bo Kyung Koo; Hye Seung Jung (Endocrinology and Metabolism, 2019)
BackgroundConflicting results have been reported on the efficacy of insulin degludec/insulin aspart (IDegAsp) compared to basal insulin in type 2 diabetes. We investigated the effects of changing basal insulin to IDegAsp on glycemic control and sought to identify factors related to those effects.MethodsIn this retrospective study of patients from three referral hospitals, patients with type 2 diabetes using basal insulin with hemoglobin A1c (HbA1c) levels less than 11.0% were enrolled. Basal insulin was replaced with IDegAsp, and data were analyzed from 3 months before to 3 months after the replacement.ResultsEighty patients were recruited (52.5% male; mean age, 67.0±9.8 years; mean duration of diabetes, 18.9±8.5 years; mean HbA1c, 8.7%±1.0%). HbA1c levels increased during 3 months of basal insulin use, but significantly decreased after changing to IDegAsp (8.28%±1.10%, P=0.0001). The reduction was significant at 6 months in 35 patients whose longer-term data were available. Patients with a measured fasting plasma glucose (m-FPG) lower than their predicted FPG (p-FPG) by regression from HbA1c showed a significant HbA1c reduction caused by the change to IDegAsp, even without a significantly increased insulin dose. However, patients whose m-FPG was higher than their p-FPG did not experience a significant HbA1c reduction, despite a significantly increased insulin dose. Furthermore, the HbA1c reduction caused by IDegAsp was significant in patients with low fasting C-peptide levels and high insulin doses.ConclusionWe observed a significant glucose-lowering effect by replacing basal insulin with IDegAsp, especially in patients with a lower m-FPG than p-FPG.